Modern Pots : Hans Coper, Lucie Rie & their Contemporaries : The Lisa Sainsbury Collection - Frankel, Cyril (Norwich : University of East Anglia, 2000)
Coper, Hans ; Rie, Lucie ; Leach, Bernard ; Hamada, Shoji ; Leach, Janet ; Godfrey, Ian ; Ward, John ; Henderson, Ewen ; Barry, Val ; Burnett, Deirdre ; Stair, Julian ; Radstone, Sara ; Jones, Christine ; Carter, Chris ; Tower, James ; Martinez, Maria ; Koch, Gabriele ; Salmon, Antonia ; Walton, Sarah ; Lee, Jennifer ; Casanovas, Claudi ; Spira, Rupert ; Liao, Chun ; Bryant, Anthony ; Partridge, Jim ; Howlett, Steve
Schenking Flanders DC
boek
Keywords: Coper, Hans; Rie, Lucie